Lanthanum-based nanoparticles: A promising frontier in antimicrobial applications - Ikhazuagbe H. Ifijen; Peter Agyemang; Emmanuel Faderin; Lovelyn Oyinyechi Odo; Emmanuel Ikechukwu Okeke; Divine Ifechukwu Onugha; Stella Eberechi Obuba; Obembe Oluwafunke; Chinyem Ogochukwu (Next Materials)
Lanthanum-based nanoparticles have garnered significant attention for their potential in antimicrobial applications due to their unique properties and mechanisms of action. This review explores the antimicrobial efficacy of various lanthanum-based nanoparticles, including La2O3, La(OH)3, and LaF3, highlighting their mechanisms of action such as disruption of microbial cell walls, generation of reactive oxygen species (ROS), and interference with microbial DNA and protein synthesis. Despite their promising attributes, several challenges hinder their practical application, including limited understanding of their mechanisms, concerns over biocompatibility and toxicity, and difficulties in scaling up production. Emerging trends in nanoparticle research, such as surface functionalization, smart delivery systems, and green synthesis methods, present innovative approaches to enhance the efficacy and sustainability of lanthanum-based nanoparticles. Additionally, integrating these nanoparticles into advanced materials and exploring combination therapies offer new possibilities for expanding their applications. Future research should focus on elucidating the detailed mechanisms of antimicrobial action, conducting comprehensive biocompatibility and environmental impact studies, and developing scalable and cost-effective synthesis methods. Addressing these challenges and embracing emerging trends will be crucial for advancing the application of lanthanum-based nanoparticles and leveraging their benefits for improved antimicrobial solutions in both clinical and industrial contexts. This review provides a comprehensive overview of the current state of research on lanthanum-based nanoparticles, identifying key areas for further investigation and highlighting their potential to revolutionize antimicrobial technology.